The Axis Alliance and Japanese-American Relations, 1941 - Schroeder, Paul W. (Cornell University Press, 2019)
Examined thoroughly and intelligently in this book is an important aspect of the Japanese-American negotiations preceding the outbreak of the war--the role played by the Tripartite Alliance between Germany, Japan, and Italy. The author shows the Tripartite Pact in a broad light, as part of the general diplomatic and political developments of the times. He considers it first as it figures in the story of Japanese-American relations; then as it fits into the history of Japanese-German relations from 1936 to 1941; and finally as it was seen by the outside world, especially by the American leaders and public.The view that American policy was Roosevelt's "back door to war" is rejected, as is the opposite view that it was the only possible answer to Japanese conspiracy and aggression. The author favors Ambassador Joseph E. Crew's opinion that American policy in the latter half of 1941 was a mistake and that a more conciliatory policy could have achieved America's essential aims without war or "appeasement."Among the author's provocative contentions is that if American policy was a mistake, it was a mistake not of the Administration or a party only, but of the whole American people.Winner of the 1956 Beveridge Award, this book provides a persuasive analysis of a complex and controversial chapter in American history.